Eco-Friendly Soap Production: Physicochemical Characterization, Cleansing Performance, and Yield Optimization Using Various Alkali and Lipid Sources - Rahman, H.; Farha, M. N.; Hossain, M. A. (Journal of Scientific Research, 2026)
An eco-friendly approach to soap production was explored using the semi-boiled saponification method with sodium methoxide (CH3ONa) as an efficient alkali. The performance of CH3ONa was compared with that of traditional alkalis (NaOH and KOH) in soap making from various vegetable oils (coconut, peanut, palm, olive, castor, and sesame) and blended oils. The soap yield and physicochemical properties, including pH, free alkali, foam stability, cleansing power, and hardness, were measured. Results showed that CH3ONa constantly produced the highest yields, up to 98 % for the coconut-sesame oil blend and 94 % for peanut oil. The pH of blended oil soaps with CH3ONa ranged from 9.60 to 10.00, which was closer to the commercial bathing soap (9.00 to 10.00). However, overall soap pH varied from 9.04 to 11.30. Free alkali was absent in most soaps, indicating proper neutralization. Coconut oil and its blends exhibited higher foam stability, cleansing ability, and balanced hardness. These findings suggest that combining CH3ONa with blended oils in saponification increases yield and optimizes physicochemical properties, providing an effective strategy for sustainable soap production in both industrial and household use.